دور رئیس المترجمين "ﭼاري" في الصراع الطیبي الأهناسي من خلال إعادة قراءة للوحتين من تلك الفترة - سعدالله، تامر محمد علي Saadullah, Tamer Mohammed Ali (جامعة مدينة السادات - كلية السياحة والفنادق, 2018)
يتناول البحث فترة الصراع الطيبي الأهناسي من خلال دراسة لوحتين لرئيس المترجمين "جاري" والذي تولي قيادة الجيش الطيبي بجانب وظيفته كرئيس للمترجمين في عهد الملك واح- عنخ- انيوتف " انيوتف الثاني" ثالث ملوك الأسرة الحادية عشر (± ٠٥٠٠٢١٠٠ 2ق.م) ، والتي تمكن من خلالها الملك" انيوتف الثاني" بعد سلسلة من المعارك بقيادة "جاري من بسط نفوذه بدءا من الأقليم الأول من مصر العليا اليفانتين حتي الأقليم العاشر من مصر العليا " كوم اشفاو" وهاتين اللوحتين تم العثور عليهما في مقبرة رئيس المترجمين "جالي " رقم٢ التي توجد في منطقة الطارف بالبر الغربي بطيبة ، وقد تم نقشهما بطريقة رديئة جدا ومفعمين بالأخطاء حتي في أسماء الأعلام ذائعة الشهرة مثل اليفانتين و العرابة المدفونة مما يدل على جهل النحات الذي نقشهما
This Paper is concerned the conflict era of the Thebes - Herkleopolis through studying two Steles of the overseer of Scouts Djari, from the eleventh dynasty cemetery of El-Tarif at Thebes. Two Stela ,found in doorway of his tomb, one with deceased standing, in Cairo Mus.Ent.41437, the other with deceased and wife seated in Brussels,Mus.roy.E.4985.Two rectangular limestone tablet carved in a style whose crudeness seems at odds with Djari,s rank. These two stela of the XIth dynasty form an interesting addition to the very small number of steles, which have been preserved of this period. The hieroglyphs are coarse and rudely cut. The two stela illustrates the southern Egyptian relief style of the first intermediate period. The autobiographical text Speaks of a war waged by the Theban king Wahankh Intef II against the Herakleopolitans. Here we may note that two stela of Djari found together refer separately to his family position and his official position both allude to the Horus Wahankh Intef II. and we know from the two stela that Djari protected the land as far north as Aphroditopolis, fifty miles north of Abydos
Keywords: التراث الفرعونى -- اللوحات الأثرية -- الصراع الطیبی الأهناسی -- مصر القديمة